Influencia en la desinfección de huevos fértiles de gallinas ponedoras pesadas de la linea ross 308 en el proceso de incubación. - Tandazo, Walter Pablo (2012)
The investigestion Influence research raised disinfecting fertile hens eggs heavy Ross 308 which aims to study the best method for the disinfection of eggs hatching. Among the objectives are: To determine the best method of disinfection of fertile eggs of chickens Ross 308 line, perform the analysis of embryonic development of eggs fertile period is determined in which embryonic death in each of the treatments and make economic analysis of the incubation. For the study employed a total of 1600 eggs disinfection treatments using fertile eggs by immersion, sprinkling, gas and without disinfection (control) four consecutive loads 400 eggs , for statistical analysis employed a completely randomized design (DCA) and applied the multiple range test Tukey 95% probability. The variables studied were: fertility (%), clear eggs (%), pollution (%), embryonic development (%), weight loss (g), and chick quality comparison bb (g) The results showed that the gas disinfection treatment had the highest fertility, egg weight before incubation, birth weight, weight loss and hatched chicks, and embryonic development in the 6.12 and 18 days. The economic analysis showed that the highest revenue, profit and cost / benefit ratio presented with gas disinfection treatment.